Peningkatan Produktivitas UMKM Melalui Penerapan dan Pelatihan TTG Perajang Aneka Keripik Sebagai Upaya Peningkatan Kesejahteraan Masyarakat - Rahayu Mekar Bisono; Wida Yuliar Rezika; Alfi Tranggono Agus Salim; Hanum Arrosida; Indarto Yuwono; Wahyu Pribadi (Abdi-mesin: Jurnal Pengabdian Masyarakat Teknik Mesin, 2022)
The impact of Covid-19 has hit Indonesia, including MSME actors and other small communities who are also engaged in the Home Industry (IRT). One of the affected communities is Jumini as a partner of the PkM program that is being proposed. Engaged in the field of typical Trenggalek snacks, Jumini has been in the business of uni for quite a long time. Due to limited equipment, especially the impact of Covid-19, partner businesses are still in the on-site stage. The long-term goal to be achieved in this PkM program is that partners can grow and develop into successful MSMEs. Therefore, because partners feel they have the capability to develop and be developed, on this occasion the proposing team chose partners as program targets. The initial target to be achieved in this program is for partners to get adequate chip choppers and increase business management capabilities. With this, it is hoped that partners will be able to develop, and if possible, will be able to work together again in the next opportunity, so that the long-term goals that have been declared can be realized. To realize this, the proposing team used an instrumental approach, with the initial step being FGDs and surveys at partner locations with the results found partners' priority problems and solutions. The solution offered is to provide appropriate technology for chopping assorted chips accompanied by training in tool operation and daily maintenance. This community service program has succeeded in solving several problems experienced by partners, especially in the aspect of raw material production. The use of TTG chopper of assorted chips can increase the efficiency of the process of chopping raw materials up to 80%. In addition, the quality of the chopping results is also better. In addition to several production factors, partners' understanding of the appropriate technology for chipping assorted chips has also increased. Partners have been able to operate the TTG chopper for assorted chips, which has increased well. Partners can also do daily maintenance themselves. In addition, the implementation of this community service program has also succeeded in increasing knowledge of business management and partner production management.